2014
DOI: 10.3201/eid2001.130353
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Infectivity in Blood of Persons with Variant and Sporadic Creutzfeldt-Jakob Disease

Abstract: We report the presence of infectivity in erythrocytes, leukocytes, and plasma of 1 person with variant Creutzfeldt-Jakob disease and in the plasma of 2 in 4 persons whose tests were positive for sporadic Creutzfeldt-Jakob disease. The measured infectivity levels were comparable to those reported in various animals with transmissible spongiform encephalopathies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 14 publications
3
73
1
1
Order By: Relevance
“…Recently, infectivity measurements in blood fractions collected from a vCJD-infected patient and those from a scrapie-infected sheep indicated that in both situations prion levels and the partition of infectivity in blood compartments are similar (10,11). This further reinforced the pertinence of data collected in TSE-infected sheep for assessing the vCJD blood-borne transmission risk.…”
Section: Importancementioning
confidence: 60%
“…Recently, infectivity measurements in blood fractions collected from a vCJD-infected patient and those from a scrapie-infected sheep indicated that in both situations prion levels and the partition of infectivity in blood compartments are similar (10,11). This further reinforced the pertinence of data collected in TSE-infected sheep for assessing the vCJD blood-borne transmission risk.…”
Section: Importancementioning
confidence: 60%
“…Moreover, a number of healthy people have been found to harbor this agent in lymphoreticular tissues (3,9,10); however, it is not known whether PrP TSE circulates in the blood of these individuals and whether they will develop the disease later in life. Recently, infectivity was reported in the plasma of two out of four patients affected by sporadic CJD (sCJD) (11). Although similar levels of PrP TSE have been detected in spleens, tonsils, and lymph nodes of vCJD and sCJD patients by Western blotting (12), the identification of this protein in the blood of individuals afflicted with the latter by various methods, including PrP TSE capture coupled to direct immunodetection of surface-bound material (6), capillary electrophoresis (13), and protein misfolding cyclic amplification (PMCA) coupled to surrounding optical fiber immunoassay (12), has been highly elusive for decades, with only two cases recently reported (8).…”
mentioning
confidence: 99%
“…Our studies here support the view that the level of prion infectivity in blood from prion-diseased individuals may be underestimated when assessed by intracerebral inoculation of rodents in comparison with bioassay of similar material in other experimental systems. This is particularly pertinent to our assessment here of prion-infected plasma that could be diluted by several orders of magnitude and still trigger a phenotypic response in the PrP transgenic Drosophila, but appears to contain a low level of infectivity when assayed in other systems [10,[15][16][17][18][19][20][21]. One possibility for the efficient detection of scrapie-infected sheep plasma by PrP transgenic Drosophila is that this invertebrate host does not normally express PrP and may therefore not have evolved suitable defence mechanisms that efficiently remove or sequester misfolded neurotoxic forms of this protein.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, these studies revealed that prion infectivity titres of blood samples harvested during the asymptomatic phase of prion disease were up to 10-fold less than those collected during the clinical phase [10,19,20,22]. Infectious prions were found to be associated with white and red blood cells, platelets and plasma, although interspecies variations existed with regard to the distribution of prion infectivity in these different blood fractions [10,[15][16][17][18][19][20][21]. Studies in ruminants have analysed bioassays of autologous whole or fractionated blood by the intravenous route [19,20].…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation